Moonlighting behavior over the business cycle - Catalina Amuedo-Dorantes; Jean Kimmel (Institute for the Study of Labor (IZA), 2005)
Using data from the 1979 National Longitudinal Survey of Youth, we examine the cyclicality by sex of moonlighting and moonlighting hours. We find that, once we account for the sample selection into employment, both men and women exhibit procyclical moonlighting probabilities. Likewise, moonlighting hours for male multiple job holders are procyclical. These findings contradict the frequent claim that moonlighting increases during economic downturns due to economic hardship. Instead, moonlighting appears responsive to growing employment opportunities during economic expansions. At any rate, the systematic variation of moonlighting over the business cycle may have implications for the procyclical nature of real wages.
Keywords: J2; 330; moonlighting; multiple job holding; business cycles; U.S.